DEVELOPING INCLUSIVE PRACTICES WITH TECHNOLOGIES FOR ONLINE TEACHING AND LEARNING: A THEORETICAL PERSPECTIVE - Passey, Don (Bordón. Revista de Pedagogía, 2017)
INTRODUCTION. The purpose of this paper is to explore ways that online learning might support the full spectrum of learners (those with specific social and emotional difficulties or mobility or physical disabilities, for example). METHOD. The paper draws out theoretical conceptions of inclusive practices for teaching and learning when activities deploy online technologies, using evidence from current literature. The scope of the paper is limited in two ways: to online learning and inclusive practices for the adult age group (those in higher, further, vocational education and training); and to practices concerned with subject and topic learning (rather than interventions addressing specific educational needs). Some existing taxonomies are used to explore initial dimensions and features, and a new theoretical framework is drawn through an inductive process of analysis. RESULTS. The theoretical framework defines key factors for online tutors to consider: possible spatial and physical barriers — access to learning, spatially within work or home environments; implications of tutor or learning focus — accommodating the demands of learning activities adopted; social focus — accommodating the social concerns and engagement of others; emotional focus — accommodating the demands and engagement of others; and cognitive focus — accommodating specific cognitive needs. DISCUSSION. The theoretical framework factors are related to specific individual characteristics that might be presented within a wide inclusive group online. These highlight key concerns that online tutors should consider in these cases. Although new tools are being developed that could allow us to monitor social and emotional shifts in individuals and groups working online, allowing for more timely tutor intervention, taking cognisance of findings from previous studies, as in the theoretical framework offered here, can nevertheless provide us with ways to at least ensure we consider the challenges already recognised when we support wide inclusive participation.